Studi Kasus: Penerapan Model Pembelajaran Make A Match dan Discovery Learning dalam Pembelajaran IPS di Kelas IV SDN Sungai Jingah 4 - Najwa Ulya Nugrahaini; Putri Normeiliani; M. Hafi Badali; Aldy Ferdiyansyah (Journal of Character and ELementary Education, 2026)
This study aims to examine the implementation of the Make A Match and Discovery Learning models in Social Studies (IPS) learning for fourth-grade students at SDN Sungai Jingah 4. The study employed a descriptive qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. The results indicate that the use of the Make A Match and Discovery Learning models, supported by the history board media, can enhance students’ motivation and engagement, particularly in historical topics. These models create an enjoyable, interactive, and collaborative learning environment. However, some challenges were identified during implementation, such as an excessive amount of material covered in a single session and a lack of variation in questions across groups. The researchers recommend distributing the material over several sessions and diversifying group assignments to optimize learning outcomes.